Penggunaan Media Crossword puzzle untuk Meningkatkan Aktivitas Belajar Fikih di Madrasah Ibtidaiyah - Lina Herlina (STIKes Ibnu Sina Ajibarang, 2024)
Teaching using effective learning strategies is very necessary to improve student learning outcomes in the learning process. Educators need to choose interesting strategies so that students do not feel bored and learning remains active and enjoyable. One strategy that can be applied is Crossword puzzles, which allows students to learn in a fun way without reducing the essence of learning, thereby increasing their enthusiasm and enthusiasm. This study aims to determine the application and effect of the Crossword puzzle learning strategy on the learning outcomes of grade III students on theme 6 subtheme 1 at MI Al Hikmah Jatiasih. This study uses a quantitative approach with a Quasi Experiment design and a Non-equivalent control group design model. The research sample consisted of 70 grade III students. The results of the descriptive analysis showed that the average post-test score in the experimental class was 81.56, while in the control class it was 72.15, which showed a significant difference in results. The independent sample t-test showed a significance value (2-tailed) of 0.007, which was smaller than 0.05, so it can be concluded that there was a significant difference between student learning outcomes in the experimental class and the control class.